The intervention tone of coaches` behaviour: Development of the assessment of coaching tone (ACT) observational coding system - Erickson, K.; Côté, J.; Horn, T. (International Journal of Sports Science and Coaching, 2015)
The importance of coaches' interactive behaviour with respect to athlete development has long been recognized. While a number of observational coding systems exist to record the instructional content of coaches' interactive behaviour, none is designed to explicitly capture the intervention tone of these interactions - 'how' coaches say what they say. The current project entailed the development of a new behavioural coding system designed to focus on the intervention tone of youth sport coaches' interactive behaviour. Behaviour categories were developed through an iterative combination of literature review and observation of recorded youth sport coaching sessions. A coder training protocol was developed and refined until coders consistently met a minimum standard of agreement with respect to both inter- and intra-rater reliability. The full coding system was then initially validated across six different team and individual youth sports in multiple contexts over a one year period. ABSTRACT FROM AUTHOR